Knockdown of TOR causing ovarian diapause in a genetically stable brachypterous strain of Nilaparvata lugens. Issue 4 (20th June 2017) - Liu, Fangzhou; Li, Kaiyin; Cai, Wanlun; Zhao, Jing; Zou, Yulan; Hua, Hongxia
Abstract: Brown planthopper (BPH), Nilaparvata lugens (Stål) (Hemiptera: Delphacidae), is one of the most damaging pests of rice crops. BPH is a migratory insect with a delayed ovarian development in migrants classified as reproductive diapause. The molecular mechanism of reproductive diapause remains unclear, although we suspect it might be regulated by one or more nutrient signaling pathways. The target of rapamycin (TOR) pathway regulates cell growth in response to nutritional information, which raised a hypothesis that TOR mediates BPH reproductive diapause. We used a pure brachypterous strain (BS) and a predominantly macropterous strain (MS) to investigate the roles of NlTOR in BPH reproductive diapause. We found that NlTOR is expressed from the nymphal to adult stages, with a higher expression level of NlTOR in BS adults at 1, 2, and 4 days posteclosion than in MS at the same time points. Injection of ds NlTOR into BS nymphs resulted in the termination of BPH female ovary development and the retardation of nymph development. We infer that TOR signaling functions in BPH reproductive diapause by regulating the expression of NlFoxA and NlVitellogenin .